ANALISIS KUALITAS PELAYANAN BPJS DAN KUALITAS PELAYANAN RUMAH SAKIT TERHADAP KEPUASAN KONSUMEN DI RUMAH SAKIT NATAR MEDIKA NATAR LAMPUNG SELATAN - Rahayu, Sri (Jurnal Manajemen Magister Darmajaya, 2016)
Since the start of the National Health Insurance launched by the government since 01 January 2014, health personnel is expected to provide good service to the participants of the guarantee both in government and private hospital hospitals. BPJS (Social Security Administering Body) Health is a management institution and Hospital as a provider of health service providers are required to provide good service quality to service user (patient) participant guarantee so that the level of satisfaction can be realized. This study aims to analyze the quality of service BPJS and hospital service quality of patient satisfaction BPJS Health program participants with indicators: Reliability, Responsiveness, Assurance, Empathy. Keywords: Quality of service BPJS, Quality of Hospital service and Customer Satisfaction. e teaching methods well or ways of teaching in accordance with students. In order to motivate the students, teachers should be more listening and responding to students suggestions and ideas.  Keywords:  the Teachers Performance, the School Environment, Students Learning Motivation